Enriched silver plasmon resonance activity on the sonochemical synthesis of ZnO flowers with α-Fe2O3 as an efficient catalyst for photo-Fenton reaction and photo-oxidation of ethanol. (April 2020) - Uma, Kasimayan; KrishnaKumar, Balu; Pan, Gung-Tin; Yang, Thomas C.-K.; Lin, Ja-Hon
Graphical abstract: Highlights: Active Ag on ZnO/α-Fe2 O3 photocatalyst by sonochemical method for an effective photo-Fenton. Various pH and concentrations of H2 O2 were examined to confirm the optimum condition for rapid degradation of MB dye. The generation of OH radicals was detected by gas-phase analysis using DRIFT measurement. Abstract: We report the preparation of flower-shaped ZnO bunches with the α-Fe2 O3 photocatalyst using the sonochemical method followed by the photodeposition of Ag nanoparticles. The Ag-ZnO/α-Fe2 O3 photocatalyst was utilized for the removal of the environmental pollutant Methylene Blue (MB) dye. From our results, it was found that the Ag-ZnO/α-Fe2 O3 photocatalyst exhibited higher photocatalytic activity when compared to ZnO/α-Fe2 O3 with the addition of H2 O2 . Moreover, the higher plasmon resonance activity of the Ag with a photocatalyst degraded the MB dye within 30 min in the presence of H2 O2 . The different pH and the molar ratio of H2 O2 were influenced by the degradation performance. In addition, the ZnO@α-Fe2 O3 and Ag-ZnO/α-Fe2 O3 photocatalysts were used for the generation of the OH radicals and the formation of formaldehyde and CO2 as analyzed by diffuse reflectance infra-red transmission (DRIFT) spectroscopy.